The Development of Edu-Detective Thinking Learning Model For Biology Students - Panggih Priyambodo; Wulandari Saputri; Winarto Winarto; Firdaus Firdaus (STAI Hubbulwathan Duri, 2022)
This study aims to: (1) produce an appropriate Edu-Detective Thinking learning model, (2) produce a practical Edu-Detective Thinking learning model, and (3) produce an effective Edu-Detective Thinking learning model to improve environmental character, science processes skill, and students' cognitive processing abilities. This type of Research Development research refers to the Borg Gall development model, which includes: (1) preliminary study and information gathering, (2) planning, (3) initial product development, (4) preliminary field testing, (5) product revision main field, (6) main field testing, (7) operational product, (8) operational field testing, (9) final product revision, (10) dissemination implementation. Data on product validity and practicality were collected using questionnaires and observation sheets. Then, the data were analyzed descriptively quantitatively. Meanwhile, the effectiveness data were collected by test questions and analyzed using the MANOVA test. The results of the study are as follows: (1) the Edu-Detective Thinking learning model is feasible to improve the environmental character, science process skills, and students' cognitive processing abilities, (2) the practical Edu-Detective Thinking learning model to improve environmental character, science process skills, and students' cognitive processing abilities, and (3) the Edu-Detective Thinking learning model is effective for improving the environmental character, science process skills, and students' cognitive processing abilities. Thus, it can be concluded that the Edu-Detective Thinking model can be an alternative learning model to improve the quality of biology learning to be more challenging and fun for students.